EFFECT OF GAME-BASED LEARNING METHOD ON PRIMARY SCHOOL PUPILS’ ACADEMIC ACHIEVEMENT IN MATHEMATICS IN ANAMBRA STATE - UGWUDE, Ifeoma Doris; Ikeokoro, Kosisochukwu Amaka (Journal of Early Childhood and Primary Education, 2026)
The unsatisfactory academic achievement among pupils in mathematics keeps persisting and as such poses concern to parents, educational administrators, and government for years. This problem seems to be compounded by the ineffective teaching methods employed by some teachers, who often resort to rote learning and memorization instead of promoting critical thinking and problem-solving skill. This study investigated the effect of the Game-Based Learning Method (GBLM) on pupils’ academic achievement in Mathematics in Anambra State. Four purposes, three research questions guided the study and four hypotheses were formulated for the study. The study adopted a quasi-experimental design, specifically a pre-test post-test non-equivalent control group design. The population comprised 218,640 primary school pupils in 1,098 public primary schools in Anambra State. A sample of 188 primary three pupils drawn through a multi-stage sampling procedure participated in the study, with 87 pupils (32 males and 55 females) in the experimental group and 101 pupils (47 males and 56 females) in the control group. The instrument for data collection was a researcher-developed Mathematics Achievement Test (MAT) consisting of 20 multiple-choice items based on plane shapes and geometry. The instrument was validated by three experts and yielded a reliability coefficient of 0.72 using KR-20. The experimental group was taught using game-based learning strategies for four weeks, while the control group received instruction through the teacher-directed method. Data collected were analyzed using mean and standard deviation to answer research questions, while Analysis of Covariance (ANCOVA) was used to test null hypotheses at 0.05 level of significance. Findings revealed that pupils taught using GBLM achieved significantly higher mean achievement scores than those taught using TDI. Both male and female pupils exposed to GBLM achieved significantly better in mathematical concepts than their counterparts in the control group. Furthermore, a significant interaction effect was found between instructional methods, and achievement. Based on the findings, it was recommended among others that teachers and curriculum planners should integrate game-based strategies into primary school Mathematics instruction to improve pupils learning outcomes.